Comparison of Effectiveness between DPP4 inhibitors combined with Versus Other Oral Hypoglycaemic Agent(s) in Diabetic patients - Haidar, Md Shameem (Bangladesh Journal of Medicine, 2019)
Background: Diabetes is global health burden of disease that requires life-long pharmacological and non-pharmacological management to prevent complications such as cardiovascular disease, retinopathy, nephropathy, and neuropathy. Treatment of type 2 diabetes is based on an interplay of patient characteristics, severity of hyperglycemia and available therapeutic options. Metformin, sulfonylureas (SU) and DPP IV inhibitor are the most studied of the oral medications used worldwide. They play a prominent initial role in the type 2 diabetes treatment algorithm recommended by the several guideline. The growing evidence on new technologies and therapeutic interventions is rapidly expanding our knowledge and ability to manage diabetes and its complications; at the same time, however, it is challenge for physicians to select appropriate medication in appropriate dose for optimal patients care. Objectives: To compare the safety and efficacy of the dipeptidylpeptidase-4 (DPP-4) inhibitors combination with other oral hypoglycaemic agent(s) in patients with type 2 diabetes and inadequate glycemic control. Materials & method: Study was conducted among 600 patients over a period of 24 months. All the patients were adult male and female type 2 diabetic patients who received regular oral anti-diabetic drug(s) and duration of T2DM for one year or more were enrolled for study. Total 150 cases were selected. Patients with Type 1 DM, pregnant women with DM and who was receiving injectable antidiabetic medications were excluded from this study. Detail demographic data were collected from the informant and recorded in structured case report form. Clinical examination and relevant investigations were done. Main outcome variable was Glycemic status (HbA1C, FBG, 2HABF). Effectiveness of drugs was evaluated by glycaemic status of the patients. Result: Maximum number of patients (38.5%) was between 31-40 years age group with mean age 37.8±9.5 years. Present study shows that, for good glycemic control, all three results (FBS, 2H ABF and HbA1c) were within targeted level in majority patients of DPP4 Inhibitor combination group. Although FBS was best result in metformin group. About 51.9% of SUs group achieved the glycemic control targets level. In case of metformin group it was in 59.8% of patients, and in combined therapy 67.1% patients shows good glycemic target. So DPP4 Inhibitor combination is better medication than other to maintain good glycemic status in type 2 DM patient, due to maximum number of patients reached all three components of result within target range. Conclusion: Diabetes is chronic illness. Good glycemic control with choosing appropriate anti-diabetic medication is pivotal for DM management. In this study it is observed that DPP4 Inhibitor combination group of drug is better than other anti-diabetic medication to maintain good glycemic status in type 2 DM patients. Bangladesh J Medicine July 2019; 30(2) : 63-70